Uji Validitas dan Reliabilitas Kuesioner Tipe Chronotype pada Remaja - Resti Kurnia Triastanti; Arini Hardianti (Yayasan Literasi Sains Indonesia, 2024)
Obesity can have a negative impact on health, and chronotype, which includes an individual's preference for bedtime, wakefulness, eating, and other activities, becomes a relevant factor in this context. Chronotype was studied using the Eveningness-Morningness questionnaire developed by Horne & Ostberg (1976), in the questionnaire there were 34 multiple-choice question items and each question had a score which could later be categorized into 2, evening type and morning type. The validity and reliability of questionnaires are crucial aspects in research to ensure that the measurement instruments used are reliable and provide accurate results. Validity reflects the extent to which the questionnaire is able to precisely measure the variables desired by the researcher. Questionnaire validity tests can be performed by applying statistical methods such as Pearson Product Moment to evaluate the extent of correlation between questionnaire scores and related variables. Questionnaire validity tests can be performed by applying statistical methods such as Pearson Product Moment to evaluate the extent of correlation between questionnaire scores and related variables. The use of the Pearson product moment correlation coefficient in validity tests allows the determination of validity by involving a comparison between r count and r table, with values close to 1 indicating a higher level of validity. Reliability test using Alpha Cronbach on the Morningness Eveningness Questionnaire with the decision that the value of the Alpha Cronbach coefficient ≥ r table (0.6) indicates the reliability of the questionnaire. In conclusion, the Eveningness-Morningness questionnaire proved valid and reliable in measuring chronotype in adolescents aged 15-17 years.